Factors that Influence Long Stroke in Woodball Sports in Musi Rawas District - Ayu Aprilia, Lisa; Pandra, Viktor; Supriyadi, Muhammad (Journal of Physical and Outdoor Education, 2024)
This study aims to determine the factors that influence long strokes and how much these factors influence long strokes in woodball sports in Musi Rawas Regency. The research method used is quantitative. The sample used was 20 athletes. Data processing using SPSS version 20. Data analysis using multiple regression analysis. The results of the study showed that there were four factors that influenced long strokes in woodball sports in Musi Rawas Regency. Namely the arm muscle strength factor ( X_1), hand grip strength ( X_2), hand eye coordination ( X_3),and concentration ( X_4). By using SPSS version 20, the regression equation Y = -12.814 + 0.452 was obtained 〖 X〗_1+ 0.256 〖 X〗_2- 0.696 X_3- 0.122 X_4. The partial test results obtained from the four (4) factors are that the arm muscle strength factor has an influence of 43.2%, the hand grip strength factor has an influence of 24.4%, the hand eye coordination factor has an influence of 13.4% and the concentration factor has an influence of 12.3%.